Contours of the post-war security system in Europe in French strategic and diplomatic assessments (1943– 1949) - I. E. Magadeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2025)
The issues of post-war settlement have always attracted the attention of researchers, yet this agenda is becoming particularly relevant amidst the ongoing dramatic transformation of international relations. In this context, the study of the mechanisms and logic behind the advent of the Yalta-Potsdam order is especially relevant. The paper aims to trace the evolution of French strategic and diplomatic assessments regarding the key parameters of the security system in Europe following the Second World War. The case of France can serve as an illustrative example of the process of a former great-power’s painful adaption to the new international realities, associated with the loss of its status. To this end, the paper not only draws on a wide range of rare archival documents, but also adapts a new theoretical framework to explicate the evolution of the French foreign policy during the formation years of the Yalta-Potsdam order — the concept of ‘hysteresis of habitus’. The latter helps to highlight the extent to which the French policy makers at that time tended to reproduce traditional practices, disregarding the changing international context. The first section shows that this political inertia was particularly common to French foreign policy planning in 1943–1944. However, it was already the period of 1945–1947 that the ‘habitus’ transformation began: French diplomacy abandoned attempts to weaken Germany as much as possible in favour of rapprochement with Great Britain and the United States. Meanwhile, the French military increasingly began to focus on the ‘Soviet threat’. The beginning of the Cold War confronted Paris with the need to integrate into the ‘Western consensus’, yet without becoming a satellite of the Anglo-Saxon powers. In these circumstances, French diplomacy in 1948–1949 focused on Western European integration. This conceptual transformation of the foreign policy ‘habitus’ manifested itself in the active engagement of France with the Western military-political blocs: the Western Union and NATO. At the same time, it revealed the fundamental inconsistency of the French foreign policy aspirations. On the one hand, France sought to ensure its independence and avoid becoming the U.S. satellite, on the other, it was in dire need of military and political guarantees and loans from the United States. Finding a balance between these components of France’s new foreign policy ‘habitus’ remained a difficult task for Paris throughout the Cold War. The author concludes that although it is possible to observe the ‘hysteresis of habitus’ effect in the French foreign policy planning during the period under consideration, the country’s leadership also demonstrated the ability to tailor its plans to the logic of the intensifying Cold War. At the same time, a number of basic components of the country’s foreign policy identity, primarily the imperative of restoring ‘greatness’, remained constants of French politics.